Risk Factor of Sedentary Lifestyle on the Incidence of Obesity During the Covid-19 Pandemic in Adolescents in Soppeng Regency - Haniarti, Haniarti; Asnita, Sri Ayu; Anggraeny, Rini; Umar, Fitriani (Jurnal Ilmiah Kesehatan (JIKA), 2024)
Obesity was a non-communicable disease that occurs due to the accumulation of excess fat in the body which can occur in all groups, including teenagers. The purpose of this study was to analyze the factors of sedentary lifestyle behavior as a risk factor for the incidence of obesity during the pandemic in early adolescents at the SMP/MTs level. The research method was analytic observational with a case control study design. The sample in this study consisted of a case group of 20 obese adolescents and a control group of 40 non-obese adolescents with a total sample of 60 people who were taken using a stratified random sampling technique. Data were analyzed using SPSS 25 to obtain the Odd Ratio (OR) value. The instrument used was the ASAQ questionnaire for adolescents aged 13-15 years at SMPN 3 Watansoppeng and MTs DDI Pattojo. The results of this study showed that sedentary lifestyle behavior was not a risk factor for obesity (OR = 8,143 > 1, CI = 0,976 – 67,944) during the Covid-19 pandemic in early adolescents at the SMP/MTs level in Soppeng Regency. Even though adolescents with high sedentary life style behavior have a risk of 8,143 times more risk than adolescents with low sedentary lifestyle behavior, this is considered insignificant because there may be other risk factors that influence the incidence of obesity, such as genetic factors and food intake. Even so, teenagers still have to increase their movement activities by exercising, playing outside the home, and reducing cell phone use.